Slow oscillation density and amplitude decrease across development in pediatric Duchenne and Becker muscular dystrophy. Issue 4 (17th December 2020) - Simon, Katharine C; Malerba, Paola; Nakra, Neal; Harrison, Amy; Mednick, Sara C; Nagel, Marni
Abstract: Study Objectives: From childhood through adolescence, brain rhythms during non-rapid eye movement (NREM) sleep show dramatic development that mirror underlying brain maturation. For example, the function and characteristics of slow oscillations (SOs, <1 Hz) in healthy children are linked to brain development, motor skill, and cognition. However, little is known of possible changes in pediatric populations with neurologic abnormalities. Methods: We measured slow oscillations in 28 Duchenne and Becker muscular dystrophy male patients from age 4 to 20 years old during overnight in-lab clinical sleep studies. We compared our pediatric patients by age to evaluate the developmental changes of SOs from childhood to early and late adolescence. Results: Consistent with the current neuro- and physically typical literature, we found greater slow oscillation density (count of SOs per minute of each sleep stage) in NREM N3 than N2, and significantly greater slow oscillation density in frontal compared to central and occipital regions. However, separating patients into age-defined groups (child, early adolescent, and late adolescent) revealed a significant age effect, with a specific decline in the rate and amplitude of SOs. Conclusions: We found that with age, pediatric patients with Duchenne muscular dystrophy show a significant decline in slow oscillation density. Given the role that slow oscillations play in memory formation and retention, it is critical to developmentally characterize these brain rhythms in medically complex populations. Our work converges with previous pediatric sleep literature that promotes the use of sleep electroencephalographic markers as prognostic tools and identifies potential targets to promote our patients' quality of life.